Fostering Employability Skills of Mechanical Technology Students through Mentoring Approach in Industrial Training Programme - Shola Francis Bakare; Azlan Bin Abdul Latib; Muhammad Sukri Saud (Universitas Diponegoro, 2020)
Mentorship can be provided in form of counseling, role model, as well as career support to a less experienced person. Mentoring differs in one circumstance to the other. It is interpreted in different ways by different individuals. The tenacity of this study is how mentoring technique can be used tactically to accomplish employability skills development. The study adopted descriptive survey with a structured questionnaire which was administered to sample size of 153 which comprises of 78 technical college teachers and 75 professionals in the industries. The data for the study was analyzed according to the formulated for the study with the aid of Statistics Package for Social Science (SPSS). Mean score and standard deviation was used to answer the research questions. The study revealed that mentoring in ITP promotes employability skills developments of technical and vocational education (TVE) students in the field of mechanical technology. The study also revealed that some factors are militating against the effectiveness of mentoring and employability skills development during industrial training programme of TVE. Based on the findings, the study concludes with certain recommendations. The mandate for the development of workforce employability skills has been on the increase in the world over. To gain access to the world of work is enormously depending upon having employability skills required by the industries. The acquisition of employability skills can be better activated when the recipients are still in the training institutions. Finally, the study presents mentoring from the perspectives of students’ industrial training programme (ITP) as a strategic approach to foster employability among mechanical technology students.